Some elements of the Ro‐Ro terminals - Maksimavičius, Ričardas (Transport, 2004)
Although sea freight accounts for the major part in ro‐ro freight transportation schedule, due and timely processing of cargo and preparation for shipment are to a particular extent affecting the ro‐ro freight duration. It is therefore essential to minimize the freight processing time at the ro‐ro terminal. Otherwise ship schedule might be interfered and even the operation of a terminal itself and port traffic is affected.  Another problem to be encountered quite often is that ro‐ro terminal is not in the position to physically accept and process the arriving freight. This is mainly pre‐conditioned by an insufficient number of terminal gateways, the shortage of customs and border control units, and inadequate parking/storage capacity and arrangement at the terminal. The presented paper provides a solution to the said problem by giving due emphasis to the proper calculation of the capacities of terminal gateways, customs and border control facilities. Thus an attempt is made to optimize the terminal operation efficiency and attractiveness and reduce the factors impairing ro‐ro freight transportation, particularly in respect of transportation time.First Published Online: 27 Oct 2010